A Critical Analysis of the Impact of Work Overload on Lecturers' Well-Being: A Case of Obafemi Awolowo University, Ile-Ife, Nigeria - Oderinde, Segun Lakin; Akintunde, Oluwatola Y.; Ajala, Iyabo Romoke (CV. Literasi Indonesia, 2024)
This study examines the impact of work overload on the well-being of lecturers at Obafemi Awolowo University, Ile-Ife, Nigeria. Work overload is a common issue faced by academic professionals, and it can lead to negative consequences for their physical and mental health. To understand the impact of work overload on the well-being of lecturers, the article provides an insight into stress and work overload. The paper also explores potential strategies to manage and mitigate work overload among lecturers. The study uses a qualitative approach and collects its data from secondary sources such as newspapers, academic journals, textbooks, theses, and dissertations, among others. The findings indicate that the lecturers face high levels of work overload, which has a significant negative impact on their physical and mental health. The study highlights the need for intervention strategies to address work overload and improve the well-being of lecturers at Obafemi Awolowo University. This study concludes that work overload has a detrimental effect on the well-being of lecturers at Obafemi Awolowo University, Ile-Ife, Nigeria.